DETERMINAN PERILAKU YANG BERHUBUNGAN DENGAN TERJADINYA UNMET NEED KB PADA PASANGAN USIA SUBUR (PUS) DI KOTA BANDAR LAMPUNG - Megaria Purba; Endang Budiati; Achmad Djamil (Malahayati Nursing Journal, 2020)
ABSTRACT : DETERMINANT BEHAVIOR THAT IS RELATED TO THE UNMET NEED KB HAPPENING IN THE PUSPING AGE PARTICIPATION IN BANDAR LAMPUNG CITY IN 2020. Introduction : Unmet family planning needs are couples of childbearing age who do not want to have any more children or spell out pregnancy but don't use contraception. Unmet family planning needs  occur  in  all  the  existing  sub-districts,  with  the  highest  occurrence  in  North  Betung Subdistrict which is 13.00%, South Betung Subdistrict is 12.66%, and Labuhan Ratu Subdistrict with 12.49% and the lowest unmet need Tanjung Karang Pusat District as much as 10.58%.Method : This type of research is quantitative, analytical research design with cross sectional approach. The population is all EFAs in Bandar Lampung City as many as 172,782 people with a sample of 439 respondents. Data analysis used univariate analysis with percentages, bivariate analysis with Chi Square and univariate analysis with logistic regression.Result :The  results  showed  that  there  was  a  relationship  between  predisposing  factors (knowledge, attitudes and work) with the unmet need for KB in EFA in Bandar Lampung City in 2020. There was no correlation between predisposing factors (economic and educational status) with the unmet need for KB in EFA in Bandar City Lampung in 2020. There is a correlation between the reinforcing factors (husband's support, the role of officers) with the unmet need for family planning at the EFA in Bandar Lampung City in 2020. There is a relationship between the enabling  factors  (exposure  to  family  planning  information)  with  the  unmet  need  for  family planning for the EFA in the city of Bandar Lampung year 2020. The dominant factor of unmet need for family planning at EFA in Bandar Lampung City in 2020 was the knowledge factor (IEC). Conclusion :For this reason, it is expected that Puskesmas in Bandar Lampung will increase health promotion activities through Information and Education Communication (IEC) on family planning by providing counseling in accordance with Puskesmas work programs. Keywords: Determinant, Behavior, Unmet Need for Family Planning, Fertile Age Couple INTISARI : DETERMINAN PERILAKU YANG BERHUBUNGAN DENGAN TERJADINYA UNMET NEED KB PADA PASANGAN USIA SUBUR (PUS) DI KOTA BANDAR LAMPUNG TAHUN 2020.Latar Belakang :Unmet need  KB  adalah pasangan usia subur  yang tidak  ingin punya anak lagi atau menjarangkan kehamilan tetapi tidak menggunakan kontrasepsi. Unmet need KB terjadi di seluruh Kecamatan yang ada, dengan kejadian tertinggi di Kecamatan Teluk Betung Utara yaitu 13,00%, Kecamatan Teluk betung Selatan yaitu 12,66%, dan Kecamatan Labuhan Ratu sebanyak yaitu 12,49% kejadian unmet need dan terendah di Kecamatan Tanjung Karang Pusat sebanyak 10.58%.Metode Penelitian : Jenis penelitian adalah kuantitatif. Desain penelitian analitik dengan pendekatan cross sectional. Populasi adalah semua PUS yang berada di Kota Bandar Lampung sebanyak 172.782 orang dengan jumlah sampel 439 responden. Analisis data menggunakan analisis univariat dengan persentase, analisis bivariat dengan Chi Square dan analisis univariat dengan regresi logistik.Hasil :Hasil penelitian menunjukkan bahwa ada hubungan faktor predisposisi (pengetahuan, sikap dan pekerjaan) dengan kejadian unmet need KB pada PUS di Kota Bandar Lampung tahun 2020. Tidak ada hubungan faktor predisposisi (status ekonomi dan pendidikan) dengan kejadian unmet need KB pada PUS di Kota Bandar Lampung tahun 2020. Ada hubungan faktor penguat (dukungan suami, peran petugas) dengan kejadian unmet need KB pada PUS di Kota Bandar Lampung tahun 2020. Ada hubungan faktor pemungkin (keterpaparan terhadap informasi KB) dengan kejadian unmet need KB pada PUS di Kota Bandar Lampung tahun 2020. Faktor dominan kejadian  unmet  need  KB  pada  PUS  di  Kota  Bandar  Lampung  tahun  2020  adalah  faktor pengetahuan (KIE).Kesimpulan :Untuk itu diharapkan Puskesmas di Bandar Lampung meningkatkan kegiatan promosi kesehatan melalui Komunikasi Informasi dan Edukasi (KIE) tentang KB dengan cara memberikan penyuluhan sesuai dengan program kerja Puskesmas. Kata Kunci           : Determinan, Perilaku, Unmet Need KB, Pasangan Usia Subur (PUS)